IRANIAN YOUTH’S IDENTITY POLITICS: COSMOPOLITAN ASPIRATIONS, SELF-REPROACH AND LIVED EXPERIENCES OF BELONGINGNESS TO THE NATION - Alireza Azeri Matin (Sanata Dharma University, 2022)
Constituting more than one-third of the country’s population, young generation in Iran are also a subnational group who have their own unique experiences of living in Iran and distinct way of defining themselves as Iranian. This has given rise to Iranian youth’s identity politics, evinced by nationwide student-led uprisings and social movements throughout the past decade. Identity politics in this sense is specified as the ways in which the young Iranians reflect on their everyday experiences in order to make sense of their belongingness to the nation. The aim of this study, however, is to elucidate the ambiguities surrounding the youth’s identities through conducting a series of focus group discussions with the most mature segment of this age group who were selected from middle-class residents of Tehran. The findings ultimately unravelled cosmopolitan aspirations, self-reproach and some other identity-making aspects of these young people’s lives.